Leclercia adecarboxylata Cholecystitis with Septic Shock in Immunocompetent Patient - Nooraldin Merza; John Lung; Ahmed Taha; Ahmed Qasim; Jill Frost; Tarek Naguib (Case Reports in Critical Care)
L. adecarboxylata is a Gram-negative rod previously named Escherichia adecarboxylata, isolated as normal flora in the gut of animals including human stool. Most reported cases refer to immunocompromised patients with polymicrobial infections and water environments. Here we present a case of 51-year-old immunocompetent female presented with nausea, vomiting, malaise, and subjective fever for few days. On examination, she was drowsy but arousable and oriented to person, place, time, and situation. Her abdomen was tender globally and more tender in the epigastric area. Vitals showed a temperature of 37°C, pulse of 110 beats/min, blood pressure of 75/50 mmHg, and oxygen saturation of 91% on room air. An HIV panel and hepatitis panel were negative. Liver and gallbladder ultrasound was performed, revealing multiple nonmobile stones with shadowing noted within the gallbladder sac, a thickened gallbladder wall, and a moderate amount of pericholecystic fluid. Broad spectrum antibiotics, crystalloid fluids, and vasopressors were initiated. A few hours after admission she developed respiratory failure for which she underwent endotracheal intubation. An ultrasound guided gallbladder drain was performed. Culture of the biliary fluid yielded pure growth of pan-sensitive L. adecarboxylata; antibiotics were narrowed accordingly. The patient was on the maximum doses of vasopressin, norepinephrine, and epinephrine with a blood pressure of 75/45 and a mean arterial pressure of 51. She passed away on the fourth day of admission.